2003
DOI: 10.1148/radiol.2292021156
|View full text |Cite
|
Sign up to set email alerts
|

Human Gallbladder Bile: Noninvasive Investigation in Vivo with Single-Voxel1H MR Spectroscopy

Abstract: Proton (hydrogen 1) magnetic resonance (MR) spectroscopy was used to study model and porcine bile in vitro. The method was subsequently developed to facilitate the acquisition of in vivo 1H MR spectra from the gallbladder bile of 10 human volunteers. Signals attributable to phosphotidylcholine and conjugated bile acid protons were observed in eight of the 10 volunteers. Phosphotidylcholine concentrations were estimated, and five values (mean = 35.8 mmol/L, SD = 9.8) were within the expected range of levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 14 publications
5
48
0
Order By: Relevance
“…The high in vivo concentration of PtdC in the gallbladder is in accordance with previous 1 H single-voxel MRS [18]. The observed PtdC chemical shift overlaps with the PEP resonance at physiological pH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high in vivo concentration of PtdC in the gallbladder is in accordance with previous 1 H single-voxel MRS [18]. The observed PtdC chemical shift overlaps with the PEP resonance at physiological pH.…”
Section: Discussionsupporting
confidence: 90%
“…Several in vitro and in vivo 31 P MRS studies of human bile [12][13][14][15] and liver tissue extracts [12,16] showed a dominant peak of phosphatidylcholine (PtdC), a typical phosphodiester and part of bile lecithin [17]. A high concentration of PtdC in the gallbladder was also previously visualized by in vivo 1 H single-voxel MRS [18]. PtdC is an essential phospholipid in mammalian cells and is produced in all nucleated cells and tissues via a choline pathway [19].…”
Section: Introductionmentioning
confidence: 94%
“…The β-glucuronidase synthesized in the pancreatic tissue may be released into the bile along with pancreatic secretions and could bring about deconjugation of bilirubin diglucuronide present in bile, liberating free GlcU. In vivo 1 H MRS of gallbladder bile is feasible and has been successfully demonstrated in humans [23] and cynomolgus monkeys [24]. Hence, the diagnosis of pancreatic cancer can be potentially performed non-invasively, without resorting to invasive procedures such as ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the collection of bile was invasive and the analysis was in vitro. An in vivo human approach is desirable, and a study by PRESCOT et al (33) indicated that the composition of bile might be studied both qualitatively and quantitatively. However, these in vivo 1 H-MR measurements at 1.5T produced a substantially reduced number of peaks, primarily owing to the low sensitivity and spectral resolution.…”
Section: Discussionmentioning
confidence: 99%